ATOM: A Mobile TOEFL App to Boost Your English Proficiency: ATOM: Aplikasi TOEFL Seluler untuk Meningkatkan Kemahiran Bahasa Inggris Anda - Pangestu, Bagus Aji Agung; Untari, Rahmania Sri (Indonesian Journal of Innovation Studies, 2023)
In the era of Industry 4.0, like today, the role of English language proficiency has become a necessity for everyone. One way to assess someone's English language proficiency is through the TOEFL test. Therefore, there is a need for supporting media to maximize someone's English language proficiency in the TOEFL test. This research aims to develop a TOEFL application as an introduction to education. The method used is R&D as developed by Borg and Gall. This study produced an Android application called "ATOM" (Mobile TOEFL Application). From the testing conducted, it was found that the product in this research is feasible in terms of material and media with an average value of 80 (feasible) from expert validation and field testing conducted on 12 students obtaining a percentage of 87.5% covering programming aspects and material. In further development, this application can be improved in terms of material and more up-to-date features. Highlights: 1. English language proficiency is crucial in the current era of Industry 4.0 and can be assessed through the TOEFL test. 2. The development of a TOEFL application, such as the "ATOM" mobile application, can serve as a supporting media to enhance one's English language proficiency. 3. The application was found to be feasible in terms of material and media through expert validation and field testing, and can be further improved with more up-to-date features.